Gynecologic Oncology: A Pocketbook - Eskander, Ramez N. (Springer, 2015)
During this age of advanced technology, there is an incredible amount of dynamic literature surrounding the diagnosis and treatment of gynecologic cancers. Despite this information surplus, house officers and junior faculty studying gynecologic oncology indicate a need for a reliable, easily accessible, streamlined resource for everyday use. Gynecologic Oncology: A Pocketbook is a collaborative effort that combines the perspectives of expert faculty and fellows in training in the field of gynecologic oncology. Not only is it incredibly portable, but the format in which the information is presented (bullet point, outline, tables and diagrams) allows for rapid access to valuable information and is unique amongst existing texts. This distinct pocketbook will provide the information needed to care for patients with gynecologic malignancies appropriately and will promote critical thinking throughout treatment